The New Partnership for Africa's Development (NEPAD) Opportunities and Challenges - Nsouli, Saleh; Funke, Norbert (Washington, D.C. : International Monetary Fund, 2003)
This paper reviews major issues involved in achieving the objectives of the New Partnership for Africa's Development (NEPAD). Using a simple framework for evaluation, the analysis highlights considerations relevant to policymakers in the areas of poverty reduction, macroeconomic policies, trade promotion, attracting capital flows, and governance and institutional reforms. The analysis also identifies risks involved in achieving NEPAD's objectives. To minimize these risks, it will be important to make some goals more operational, to further broaden and deepen stakeholder participation, to establish a sound basis for monitoring progress, to prepare contingency plans, and to harmonize the role of regional institutions with NEPAD initiatives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet